Americium solubility and solubility limiting solid phase (SLSP) analysis in groundwater of Beishan, a proposed site for the disposal of high-level radioactive waste in China. (May 2023) - Yang, Sen; Li, Zeqin; Pan, Pujing
Abstract: The disposal of high-level radioactive waste (HLW) in deep geological repository requires reliable data including the solubility and speciation of americium and other actinides in safety assessment. In this work, a generic thermodynamic equilibrium model using the geochemical codes PHREEQC-3 and PhreePlot was used to investigate the solubility of americium in the groundwaters of Beishan in the possible ranges of pH (6–11) and PCO2 (10 −5.5 - 10 −2.5  bar). The pH-logPCO2 diagram of solid phases and aqueous species of Am was computed and plotted with Am solubility contour lines. The results indicate that the solubility of Am under the repository far-field conditions is dependent on pH and under the near-field conditions on pH and PCO2 . Based on our calculations, we have determined that AmCO3 OH·0.5H2 O( cr ) is thermodynamically stable in both the near- and far-field conditions, leading to an Am solubility of 4.0 × 10 −9  mol/kg and 1.5 × 10 −8 mol/kg under, respectively, the near- and far-field conditions of the proposed Beishan repository. However, the amorphous AmCO3 OH( am, hyd ) phase, while thermodynamically metastable, is expected to persist for an extended period of time, possibly hundreds of years or more after the closure of a repository. As such, it is assumed to be the solid phase that limits the solubility of americium, leading to much enhanced Am solubilities of 6.3 × 10 −7 and 2.4 × 10 −6 mol/kg for the Beishan near- and far-field conditions, respectively. Therefore, solely based on the solubility data, Am could be more toxic than the natural uranium in the Beishan granitic groundwater within ∼5000 years after the proposed repository's closure. It is thus important to ensure that Am is well contained by the engineered barriers within this timeframe. Since Am solubilities in Beishan groundwater are rather low, the effect of sorption and colloidal formation could be potentially more important for Am migration in groundwaters, however further studies are required before these processes can be properly evaluated. Highlights: PHREEQC-3 was used with evaluated thermodynamic data to establish the solubility and speciation of Am in Beishan groundwaters. The solid phase AmCO3 OH·0.5H2 O( cr ) was found to be stable under both near- and far-field conditions in Beishan. The solubility limiting solid phase in Beishan groundwater was assumed to be the metastable AmCO3 OH( am, hyd ). Am solubility was calculated to be 6.3 × 10 −7 mol/kg and 2.4 × 10 −6 mol/kg under near- and far-field conditions, respectively. If not contained, Am could pose a health hazard in Beishan groundwater within ∼5000 y after the proposed repository's closure.